Motivational profile for physical exercise: a retrospective cohort - Ramon Gustavo de Moraes Ovando; Lorena Laira Morais dos Santos; Sonia Maria Marques Gomes Bertolini (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The objective of the study was to analyze the type of motivation, from the point of view of self-determination, in individuals who sought to practice physical activity in a certain period of their lives and its relationship with sociodemographic and clinical characteristics. This is a retrospective cohort study, with an interval of 12 years. The survey was carried out in 2019 in two moments. Initially, secondary data were collected from 40 individuals enrolled in a gym between 2007 and 2009, then these same individuals were collected primary data. Sociodemographic, clinical and motivational profile variables of the participants were investigated. Of the 40 individuals who participated in the second moment, 35% did not continue to practice physical activity in the last 12 months (Gno), while 65% (Gyes) continued. The results appreciated that Gyes, when compared to Gno, are more autonomously motivated (p < 0.01). The mean external regulation score, however, differs between groups, being higher for the Gno group (p < 0.01, for obese individuals (p < 0.01); in relation to the presence of diabetes (p<0.01) and in relation to the presence of the three diseases (hypertension, diabetes and dyslipidemia) together (p=0.01). Thus, it is concluded that physically active individuals for prolonged periods are more self-determined for the practice of physical exercises.